Improvement of modal matching image objects in dynamic pedobarography using optimization techniques - João Manuel Ribeiro da Silva Tavares (2010)
This paper presents an improved approach for matching objects represented in dynamic pedobarography image sequences, based on finite element modeling, modal analysis and optimization techniques. In this work, the determination of correspondences between objects data points is improved by using optimization techniques and, because the number of data points of each object is not necessary the same, a new algorithm to match the excess points is also proposed. This new matching algorithm uses a neighbourhood criterion and can overcome some disadvantages of the usual one to one matching. The considered approach allows the determination of correspondences between 2D or 3D objects data points, and is here apply in dynamic pedobarography images.